Reptile expos: an analysis and recommendations for control - Warwick, Clifford; Steedman, Catrina; Jessop, Mike; Grant, Rachel (Frontiers in Animal Science, 2024)
Reptile expos are typically itinerant events at which live wild-caught and/or captive-bred turtles, tortoises, crocodiles, lizards, and snakes are displayed, sold, or exchanged for pet keeping purposes. We conducted a literature review and analysis of reports regarding animal welfare and public health issues of concern associated with the display and sale of reptiles at expos in Europe and North America. We also conducted a limited survey of several relevant government authorities to briefly appraise existing situations regarding governance and law internationally, and performed a further limited examination of online advertisements in order to estimate the number of events. In addition, we conducted an analysis comparing husbandry standards for reptile expos versus other animal display or sale situations using UK formal legal guidance, which adopts the Five Welfare Needs as a basis. Finally, we also conducted a SWOT (strengths, weaknesses, opportunities, and threats) analysis of key features associated with reptile expos. We identified at least 10 animal welfare and 5 public health and safety problems as occurring and endemic to the typical operation of reptile expos. Comparisons between the ways in which animal welfare and public health issues are regarded or managed for reptile expos in relation to, for example, traditional zoos, mobile zoos, and pet sales are stark and concerning, with expos constituting the least protective and potentially most harmful situations out of all captive reptile-keeping scenarios. The lack of monitoring and control of reptile expos, combined with their frequent occurrence, strongly indicates the requirement to urgently control and prohibit these events. We recommend that where reptile expos are already essentially prohibited such bans should be immutable and not subject to any weakening provisions. Where reptile expos are permitted and/or subject to limiting conditions, or where reptile expos are not subject to limiting conditions, then our recommended 40 stipulations and overarching control principles should be applied as interim mitigating measures pending the introduction of prohibitions or ‘bans’. Governments should aim to ensure that enforcement of such measures is robust.